Study on the Incidental Consequences of Crime in the Era of Misdemeanor Era - Tang, Junyi (Transactions on Social Science, Education and Humanities Research, 2024)
Under the background of the misdemeanor era, the normative concept and functional orientation of the incidental consequences of crime have changed. Incidental consequences of crime refer to the adverse consequences that are stipulated outside the criminal law and apply to criminals or their relatives, which detract from social evaluation or increase the burden of obligations. The functional orientation is also different in the eras of misdemeanor and felony. There is no distinction between the incidental consequences of misdemeanors and felonies, which violates the principle of proportionality, and the principle of prohibiting repeated evaluation. The negative effects are becoming more obvious. We should strengthen the correlation between the incidental consequences of crime and the preconditions that trigger the consequences, adjust the conflicts between the provisions of different ranks of effectiveness, and adjust the provisions on the incidental consequences of criminals and non-criminals to follow the principle of proportionality so that the incidental consequences of crime can be more appropriately applied in the era of misdemeanors.